Study of general practice consultations and menopausal problems. Oxford General Practitioners Menopause Study Group. Issue 6771 (2nd February 1991) - Barlow, D H; Brockie, J A; Rees, C M
Abstract : OBJECTIVE–To investigate the nature of work related to the menopause in general practice. DESIGN–Questionnaire study over six months among general practitioners after each consultation with a woman aged 40-69 at which issues related to the climacteric had been discussed. SETTING–9 General practices in the Oxford area. SUBJECTS–416 Women who had 572 consultations. MAIN OUTCOME MEASURES–Age, menopausal state, and first or subsequent consultation. Symptoms were classified together with the treatment and the outcome of the consultation. RESULTS–The consultation rate varied greatly between practices, the overall rate being 4.4%. There were many premenopausal women and women in their 60s presenting; women with hysterectomies presented more often–36% (37/103) of women with hysterectomies had more than one consultation compared with 26% (38/144) for premenopausal women and 24% (38/155) for postmenopausal women. 409 women had symptoms and 218 were prescribed oestrogen treatment. 156 of the consultations involved discussion and advice only. Only four women were referred to a local specialist clinic. CONCLUSION–There is a low overall use of hormone replacement therapy in the general postmenopausal population despite the recent media coverage of its benefits in the prevention of osteoporosis and subsequent fractures.